1-methyl-2-vinylpyrrole and 1-phenyl-3,4-dimethylphosphole: Their coordination chemistries and reactivities in a chiral palladium complex promoted asymmetric Diels-Alder reaction - Loh, S.-K. (2014)
10.1016/S0957-4166(98)00012-3